Disease control with prior platinum-based chemotherapy is prognostic for survival in patients with metastatic urothelial cancer treated with atezolizumab in real-world practice - Mencinger Marina (Sciendo, 2021)
Atezolizumab, a programmed-death ligand-1 (PD-L1) inhibitor, is a novel treatment option for patients with metastatic urothelial cancer (mUC). Clinical prognostic factors, survival outcomes, and the safety of patients with mUC treated with atezolizumab, in a real-world setting, were investigated.